IDENTIFICATION OF THE FACTORS AFFECTING STUDENTS AT SANATA DHARMA - Hendra Michael Aquan; Luisa Diana Handoyo; Paulus Wiryono Priyotamtama (LINGUA : JURNAL ILMIAH, 2022)
The pandemic COVID-19 has disrupted global society and its order, including the educational sector. Amid the pandemic, students of Sanata Dharma University Yogyakarta felt the impact. Reports from other countries indicated the pandemic situations to increase levels of stress and anxiety among college students. Sometimes, a difficult situation does not always cause negative responses. Some studies suggested that the pandemic may affect positive attitudes (optimism). This study aimed to find factors that contribute in developing optimism attitude among college students of Sanata Dharma University. Researchers employed online questionnaire to gather informations from 137 respondents. Three methods of analysis: exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM) were used. Results indicated reasoning and experience as independent variables, and optimism as a dependent variable. Factor of type of information was suggested as mediating variable. Further, a structural model reported that Goodness of fit indices from the model: χ2 = 63.922 (df = 55; alpha = 0.05), probability = 0.192, CMIN/DF = 1.162(≤ 2.00), RMSEA = 0.023 (≤ 0.08), GFI = 0.970 (≥ 0.90), TLI = 0.985 (≥ 0.90).